Clinical trials of disease-modifying therapies for neurodegenerative diseases: the challenges and the future - Lang, Anthony E (Nature medicine, 2010)
Neurodegenerative diseases such as Parkinson's disease and Alzheimer's disease represent a crucial and exponentially increasing challenge to health care systems throughout the world. There is an urgent need for effective treatments that will both delay their onset and slow their inexorable progression. Many obstacles stand in the way of realizing these goals. It is expected that future advances will have a major impact on how and when the diagnosis will be made. It is hoped that these will eventually make it possible to initiate effective disease-modifying therapies long before the neurodegenerative process becomes established and symptomatic.